Bacterial Patterns and Antibiotic Resistance Profiles at Advent Hospital Bandar Lampung, January–June 2025 - Hidayat Hidayat; M. Azzaky Bimandama (Journal of Health and Nutrition Research, 2026)
Antimicrobial resistance (AMR) poses a significant global health threat, necessitating local surveillance to guide empirical therapy and antimicrobial stewardship. This study aimed to characterize the distribution of bacterial pathogens and their antibiotic resistance profiles at Advent Hospital Bandar Lampung. A descriptive cross-sectional study was conducted using 171 clinical specimens collected from January to June 2025. Bacterial identification and antimicrobial susceptibility testing were performed in accordance with CLSI guidelines. The 171 specimens, 91 yielded bacterial growth, dominated by Gram-negative organisms—specifically Klebsiella pneumoniae and Escherichia coli. Gram-negative isolates exhibited high resistance to ampicillin and third-generation cephalosporins, whereas meropenem, amikacin, cefoperazone-sulbactam, and piperacillin-tazobactam remained effective. Gram-positive pathogens, primarily Staphylococcus aureus, showed substantial β-lactam resistance but maintained susceptibility to vancomycin, linezolid, and gentamicin. Critical phenotypes identified included carbapenem-resistant Acinetobacter baumannii (CRAB), third-generation cephalosporin-resistant Enterobacterales (3GCRE), and methicillin-resistant S. aureus (MRSA). The high prevalence of AMR in this setting underscores the urgent need to update empirical treatment guidelines, strengthen antimicrobial stewardship programs, and enhance infection prevention and control measures.